2017
DOI: 10.1183/13993003.01880-2016
|View full text |Cite
|
Sign up to set email alerts
|

The association between chronic airflow obstruction and poverty in 12 sites of the multinational BOLD study

Abstract: Poverty is strongly associated with mortality from COPD, but little is known of its relation to airflow obstruction.In a cross-sectional study of adults aged ≥40 years from 12 sites (N=9255), participating in the Burden of Obstructive Lung Disease (BOLD) study, poverty was evaluated using a wealth score (0-10) based on household assets. Obstruction, measured as forced expiratory volume in 1 s (FEV)/forced vital capacity (FVC) (%) after administration of 200 μg salbutamol, and prevalence of FEV/FVC Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 19 publications
4
46
0
4
Order By: Relevance
“…It was reported that 47% of asthmatic children were unrecognized and only 3% of these children were on daily treatments . Townend et al , have also reported a high prevalence of airway obstruction, to be significantly associated with poverty in several countries. At the international level, the importance of adequate, accessible, and sustainable housing in the cities by 2030 is one of the targets of the recent Sustainable Development Goal on sustainable cities, while at the national level, housing the poor is an integral part of developmental policies.…”
Section: Introductionmentioning
confidence: 95%
“…It was reported that 47% of asthmatic children were unrecognized and only 3% of these children were on daily treatments . Townend et al , have also reported a high prevalence of airway obstruction, to be significantly associated with poverty in several countries. At the international level, the importance of adequate, accessible, and sustainable housing in the cities by 2030 is one of the targets of the recent Sustainable Development Goal on sustainable cities, while at the national level, housing the poor is an integral part of developmental policies.…”
Section: Introductionmentioning
confidence: 95%
“…It is important that governments are made aware that COPD can no longer be seen as a condition solely caused by smoking in adult life, although this is certainly a major risk factor. From a global perspective, exposure to biomass fumes and air pollution in adult life are important risk factors and there is now good evidence that poor pre-and post-natal lung growth as a result of malnutrition, infections and/or passive exposure to pollutants also leads to COPD [3][4][5]. The contribution of these different risks factors varies.…”
Section: @Erspublicationsmentioning
confidence: 99%
“…Susceptibility to infection and inflammatory lung disease may also be affected by poor nutrition, reduced immunity and poverty [11]. Biomass fuels are used by the poorest people and epidemiological studies showing an association between biomass smoke and COPD may be confounded by poverty [12]. Globally poverty is important in COPD, as COPD mortality rates relate to poverty; whereas COPD prevalence rates are more closely related to tobacco smoking [13].…”
mentioning
confidence: 99%